Influence of Spatial and Chromatic Noise on Luminance Discrimination. Issue 1 (December 2017) - Miquilini, Leticia; Walker, Natalie; Odigie, Erika; Guimarães, Diego; Salomão, Railson; Lacerda, Eliza; Cortes, Maria; Lima Silveira, Luiz; Fitzgerald, Malinda; Ventura, Dora; Souza, Givago
Abstract Pseudoisochromatic figures are designed to base discrimination of a chromatic target from a background solely on the chromatic differences. This is accomplished by the introduction of luminance and spatial noise thereby eliminating these two dimensions as cues. The inverse rationale could also be applied to luminance discrimination, if spatial and chromatic noise are used to mask those cues. In this current study estimate of luminance contrast thresholds were conducted using a novel stimulus, based on the use of chromatic and spatial noise to mask the use of these cues in a luminance discrimination task. This was accomplished by presenting stimuli composed of a mosaic of circles colored randomly. A Landolt-C target differed from the background only by the luminance. The luminance contrast thresholds were estimated for different chromatic noise saturation conditions and compared to luminance contrast thresholds estimated using the same target in a non-mosaic stimulus. Moreover, the influence of the chromatic content in the noise on the luminance contrast threshold was also investigated. Luminance contrast threshold was dependent on the chromaticity noise strength. It was 10-fold higher than thresholds estimated from non-mosaic stimulus, but they were independent of colour space location in which the noise was modulated. The present study introduces a new method to investigate luminance vision intended for both basic science and clinical applications.